Efficacy of Biopesticide Be-Bas against Sweet Potato Weevils (Cylas formicarius Fabricius) in Tidal Land - Yusmani Prayogo; Marida Santi Yudha Ika Bayu (Jurnal Perlindungan Tanaman Indonesia, 2019)
In Indonesia tidal land is very wide and quite potential for sweet potatoes, but an obstacle for this cultivation is sweet potato weevil (Cylas formicarius) causes loss of 100%. This research aimed to evaluate the efficacy of biopesticide Be-Bas contains Beauveria bassiana entomopathogenic conidia to C. formicarius mortality at tidal lands. This study was conducted on June-November 2016 in South Kalimantan. The research consisted of five treatments and five replications. Results showed that the application of biopesticide Be-Bas in the planting hole and stem base was effective to cause mortality of 17 and 15 larvae per tuber, respectively. However, the application by soaking cutting was able to kill 3 larvae per tuber. The application of biopesticide Be-Bas in the planting hole and stem base were also effective to suppress the number of eggs laid by C. formicarius in the tuber, hence there was no damage found on the tuber. Meanwhile, the application of conventional insecticide was less effective because a total of 17 eggs and 3 larvae of C. formicarius were still found in each tuber. It caused tuber damage up to 17%, thus the tuber cannot be consumed. Therefore, the application of biopesticide Be-Bas in the planting hole or stem base was considered capable to suppress tubers damage caused by C. formicarius better than that of conventional insecticide.